Edukasi Waspada Kolesterol Tinggi Di Desa Pasar X Dusun III Kecamatan Kutalimbaru - Harahap, Indah Pratiwi; Rahman, Shahrul (Jurnal Ilmiah Wahana Pendidikan, 2025)
The problem of high cholesterol (hypercholesterolemia) is one of the groups of non-communicable diseases (NCDs) whose prevalence is currently increasing. The increase in NCDs can be triggered by several factors that are closely related to the food consumed in everyday life that triggers an increase in cholesterol. This community service counseling aims to provide education related to cholesterol problems and increase public knowledge related to matters relating to high cholesterol. This education program uses visual aids such as posters and involves participants through interactive discussions. Based on the counseling, the education program regarding the problem of being aware of high cholesterol has succeeded in increasing public knowledge of the risk of increasing cholesterol, symptoms, and prevention. Although there are challenges when delivering education to participants, using visual media that has an attractive appearance can help to attract the attention of participants, where participants initially had limited knowledge about cholesterol until they gained new knowledge about high cholesterol and the importance of preventing it. With this counseling, it can be emphasized regarding education on how to prevent increased cholesterol and recognize the risks and symptoms early in order to prevent complications.